Antineoplastic Activity of Water-Soluble Form of Novel Kinase Inhibitor 1-(4-Chlorobenzyl)-3-chloro-4-(3-trifluoromethylphenylamino)-1H-pyrrole-2,5-dione immobilized on Polymeric Poly(PEGMA-co-DMM) Carrier - Nataliya Finiuk; Olga Klyuchivska; Nataliya Mitina; Halyna Kuznietsova; Kateryna Volianiuk; Alexander Zaichenko; Volodymyr Rybalchenko; Rostyslav Stoika (MDPI AG, 2022)
The maleimide derivative 1-(4-chlorobenzyl)-3-chloro-4-(3-trifluoromethylphenylamino)-1H-pyrrole-2,5-dione (MI-1) was synthesized as inhibitor of several protein kinases, however, its application is hindered by its poor water solubility. In this study, the mechanisms of the antineoplastic action of MI-1 and its MI-1/M5 complex with M5 carrier (poly (PEGMA-co-DMM)) towards human colon carcinoma HCT116 cells were investigated by using the MTT and clonogenic assays, DNA intercalation with methyl green replacement, alkaline DNA comet assay, and Western-blot analysis. MI-1 compound and its MI-1/M5 complex possessed high toxicity towards colon (HCT116), cervical (HeLa) carcinoma cells and melanoma (SK-MEL-28) cells with GI50 value in a range of 0.75-7.22 µg/mL, and demonstrated high selectivity index (SI ˃ 6.9). The p53 status of colon cancer cells did not affect the sensitivity of these cells to the treatment with MI-1 and its MI-1/M5 complex. M5 polymer possessed low toxicity towards studied cells. The MI-1, MI-1/M5, and M5 only slightly inhibited growth of the pseudo-normal HaCaT and Balb/c 3T3 cell lines (GI50 ˃ 50 μg/mL). The MI-1 and its MI-1/M5 complex induced mitochondria-dependent pathway of apoptosis, damage of the DNA, and morphological changes in HCT116 cells, and affected the G2/M transition checkpoint. The MI-1 intercalated into the DNA molecule, while such capability of MI-1/M5 complex and M5 polymer was much lower. Thus, poly (PEGMA-co-DMM) might be a promising carrier for delivery of the maleimide derivative, MI-1, a novel kinase inhibitor, through improving its solubility in aqueous media and enhancing its antiproliferative action towards human tumor cells. Studies are in progress on the treatment of Nemeth-Kellner lymphoma (NK/Ly)-bearing mice with the MI-1 and MI-1/M5 complex.